Uganda : Technical Assistance Report-Developing the Charter for Fiscal Responsibility. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2017)
This Technical Assistance Report discusses recommendations for developing a 'Charter for Fiscal Responsibility' in Uganda. Publication of a 'Charter for Fiscal Responsibility' at the start of each new Parliament is a requirement of Uganda's new Public Financial Management Act. The Charter should set out measurable medium-term objectives for fiscal policy, and explain the methodology, data, and procedures by which performance against the objectives would be measured. The Charter should also be used to develop transparent fiscal reporting requirements and establish the role of fiscal objectives in underpinning the annual budget process.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet